ANALISIS PENDAPATAN HOME INDUSTRY PEUYEUM KETAN DI DESA TARIKOLOT KECAMATAN CIBEUREUM KABUPATEN KUNINGAN PROVINSI JAWA BARAT - Feby Dea Suryani; Arfida Boedirochminarni; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2021)
This study aims to determine the income analysis of peuyeum sticky rice home industry in Tarikolot Village, Cibeureum District, Kuningan Regency, West Java Province. Observing the industrial development in an area such as Kuningan, there are still many developing industries such as the Peuyeum Ketan industry which is managed by small industries or household activity units that aim to cover their economic needs. Based on the research results, the total revenue in the Peuyeum home industry produces 60 to 200 buckets in one production process. The average total revenue at the peuyeum home industry was IDR 7,105,833 with an average production volume of 106 buckets, while the average profit at 30 peuyeum sticky rice home industries in Tarikolot Village was IDR 1,226,250 per one-time production. The total cost of production consists of fixed costs and variable costs with an average total cost of Rp 5,879,583. The peuyeum sticky rice industry is declared profitable or feasible to continue because the average value of R / C generated is 1.20> 1, meaning that the total income earned is greater than the total costs incurred.